ANTI-COLONIAL BOOK CLUBS: CREATING A DIFFERENT KIND OF LANGUAGE FOR A NEW CONSCIOUSNESS - Carroll, Shawna M. (Art/Research International)

(untitled) (University of Alberta, 2021)
What possibilities does reading anti-colonial and counternarrative fiction have? By “plugging in” Coloma’s constitutive subjectivities, Anzaldúa’s new consciousness, and Sumara’s embodied action, I share the possibilities with the explanation of an anti-colonial book club. Part of a larger research project conducted with a feminist Deleuzian methodology, this paper focuses on one of the “hot spots” that arose during the reading processes of two participants in the book club. Through their self-reflection during their reading processes, the counternarrative and anti-colonial fiction gave the women a different kind of language which allowed them to build a stronger trust in themselves, their subject positions, and their experiences of marginalization outside of a white settler colonial discursive lens. This building of trust by creating a different kind of language to explain their subject positions and experiences of marginalization created a new consciousness that allowed them to continue subverting simplified white settler colonial understandings of who they are.